Corrosion and wear resistant nickel-based alloy
Patent Information
- Application Number
- JP2021522960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-26
- Filing Date
- 2019-10-25
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2039-10-25
Smart Images

Figure 0007641218000006 
Figure 0007641218000007 
Figure 0007641218000008
Abstract
Description
[Technical field]
[0001] [Incorporation by reference of any prior application] This application claims priority to U.S. Patent Application No. 62 / 751,020, entitled “Corrosion and Wear-Resistant Nickel-Based Alloy,” filed October 26, 2018, which is incorporated herein by reference in its entirety.
[0002] [Technical field] Embodiments of the present disclosure generally relate to nickel-base alloys that may be suitable feedstocks for hardfacing processes such as plasma transferred arc (PTA), laser cladding hardfacing processes, including high velocity laser cladding, and thermal spray processes, such as high velocity oxygen fuel (HVOF) thermal spraying. [Background technology]
[0003] [Description of Related Art] Abrasive and corrosive wear is a major problem for operators in applications involving sand, rock, or other hard media that abrade surfaces. Applications where significant wear occurs typically use high hardness materials to make the material less susceptible to failure due to severe wear. These materials typically contain carbides and / or borides as hard precipitates that make the material less susceptible to abrasion and increase the bulk hardness of the material. These materials are often applied as coatings known as hardfacings by various welding processes or cast directly onto the part.
[0004] Another major problem for operators is corrosion. In applications where severe corrosion occurs, typically high chromium soft nickel-based or stainless steel type materials are used. In these types of applications, there should be no cracks in the build-up layer as this would result in corrosion of the underlying substrate.
[0005] Currently, it is common to use either wear-resistant or corrosion-resistant materials, as few alloys exist that meet both requirements. Current materials often do not provide the required service life or require the addition of carbides to increase wear resistance, which can lead to cracking. Summary of the Invention
[0006] Disclosed herein is an embodiment of a raw material containing, by weight percent, Ni, C: 0.5-2, Cr: 10-30, Mo: 5.81-18.2, and Nb+Ti: 2.38-10.
[0007] In some embodiments, the raw material may further include, by weight percent, C: about 0.8 to about 1.6, Cr: about 14 to about 26, and Mo: about 8 to about 16. In some embodiments, the raw material may further include, by weight percent, C: about 0.84 to about 1.56, Cr: about 14 to about 26, Mo: about 8.4 to about 15.6, and Nb + Ti: about 4.2 to about 8.5. In some embodiments, the raw material may further include, by weight percent, C: about 8.4 to about 1.56, Cr: about 14 to about 26, Mo: about 8.4 to about 15.6, Nb: about 4.2 to about 7.8, and Ti: about 0.35 to about 0.65. In some embodiments, the raw material may further include, in weight percent, about 1.08 to about 1.32 C, about 13 to about 22 Cr, about 10.8 to about 13.2 Mo, and about 5.4 to about 6.6 Nb. In some embodiments, the raw material may further include, in weight percent, about 1.2 C, about 20 Cr, about 12 Mo, about 6 Nb, and about 0.5 Ti.
[0008] In some embodiments, the feedstock is a powder. In some embodiments, the feedstock is a wire. In some embodiments, the feedstock is a combination of wire and powder.
[0009] Also disclosed herein are embodiments of hardfacing layers formed from the feedstock materials as disclosed herein.
[0010] In some embodiments, the hardfacing layer comprises hard phases with a Vickers hardness of 1,000 or greater that total 5 mol % or greater, a combined total of chromium and molybdenum of 20 wt % or greater, separate hypereutectic hard phases that total 50 mol % or greater of the total hard phase fraction, a WC / Cr3C2 ratio of 0.33 to 3, a 250 mm 3 and a Vickers hardness of 650 or greater.
[0011] In some embodiments, the hardfacing layer may have a Vickers hardness of 750 or greater. In some embodiments, the hardfacing layer may exhibit no more than two cracks per square inch, have an adhesion of 9,000 psi or greater, and have a porosity of 2% by volume or less. In some embodiments, the hardfacing layer may have a porosity of 0.5% by volume or less. In some embodiments, the hardfacing layer may have a corrosion rate of 1 mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the hardfacing layer may have a corrosion rate of 0.4 mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the hardfacing layer may have a corrosion rate of less than 0.1 mpy in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61. In some embodiments, the hardfacing layer may have a corrosion rate of less than 0.08 mpy in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61.
[0012] In some embodiments, the nickel matrix can have a matrix similarity of 80% or more compared to a corrosion-resistant alloy defined as Ni:balance, X>20% by weight, where X represents at least one of Cu, Cr, or Mo. In some embodiments, the corrosion-resistant alloy is selected from the group consisting of Inconel® 625, Inconel 622, Hastelloy® C276, Hastelloy X, and Monel® 400.
[0013] In some embodiments, the hardfacing layer may be applied to hydraulic cylinders, tension risers, mud motor rotors, or oil field component applications.
[0014] Further disclosed herein are embodiments of a feedstock comprising nickel, the feedstock being configured to form, under thermodynamic equilibrium conditions, a corrosion-resistant matrix characterized by having a total of 5 mole % or more of hard phases with a Vickers hardness of 1,000 or greater and a matrix closeness of 80% or greater when compared to known corrosion-resistant nickel alloys.
[0015] In some embodiments, the known corrosion resistant nickel alloy may be represented by the composition Ni:balance, X>20 wt.%, where X represents at least one of Cu, Cr, or Mo.
[0016] In some embodiments, the raw material may be a powder. In some embodiments, the powder may be made by an atomization process. In some embodiments, the powder may be made by an agglomeration and sintering process.
[0017] In some embodiments, the corrosion resistant matrix may be a nickel matrix containing a combined total of chromium and molybdenum of 20% or more by weight. In some embodiments, under thermodynamic equilibrium conditions, the corrosion resistant matrix may be characterized as having separate hypereutectic hard phases that together total 50 mol % or more of the total hard phase fraction.
[0018] In some embodiments, the known corrosion resistant nickel alloy may be selected from the group consisting of Inconel 625, Inconel 622, Hastelloy C276, Hastelloy X, and Monel 400.
[0019] In some embodiments, the raw material may include C: 0.84-1.56, Cr: 14-26, Mo: 8.4-15.6, Nb: 4.2-7.8, and Ti: 0.35-0.65. In some embodiments, the raw material may further include B: about 2.5-about 5.7, and Cu: about 9.8-about 23. In some embodiments, the raw material may further include Cr: about 7-about 14.5.
[0020] In some embodiments, under thermodynamic equilibrium conditions, the corrosion-resistant matrix can be characterized as having a total of 50 mole % or more of hard phases and a liquidus temperature of 1550K or less.
[0021] In some embodiments, the raw materials may include a mixture of Monel and at least one of WC or Cr3C2.
[0022] In some embodiments, the raw material is selected from the group consisting of 75-85% WC + 15-25% Monel, 65-75% WC + 25-35% Monel, 60-75% WC + 25-40% Monel, 75-85% Cr3C2 + 15-25% Monel, 65-75% Cr3C2 + 25-35% Monel, 60-75% Cr3C2 + 25-40% Monel, 75-85% WC / Cr3C2 + 15-25% Monel, 65-75% WC / Cr3C2 + 25-35% Monel, and 60-75% WC / Cr3C2 + 25-40% Monel, by weight.
[0023] In some embodiments, the WC / Cr3C2 ratio of the corrosion-resistant matrix can be 0.02 to 5 by volume. In some embodiments, the thermal spray feedstock can include wire. In some embodiments, the thermal spray feedstock can include a combination of wire and powder.
[0024] Also disclosed herein are embodiments of hardfacing layers formed from the feedstock materials as disclosed herein.
[0025] In some embodiments, the hardfacing layer is 250 mm 3 The hardfacing layer may include an ASTM G65A abrasion loss of less than 1.0 mm and no more than 2 cracks per square inch when the hardfacing layer is formed from a PTA or laser cladding process. In some embodiments, the hardfacing layer may include an impermeable HVOF coating that exhibits a corrosion rate of 1 mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment.
[0026] In some embodiments, the hardfacing layer may further include a Vickers hardness of 650 or greater, and an adhesion of 9,000 psi or greater when the hardfacing layer is formed from an HVOF thermal spray process.
[0027] In some embodiments, the hardfacing layer may be applied to hydraulic cylinders, tension risers, mud motor rotors, or oil field component applications.
[0028] In some embodiments, the hardfacing layer may include a Vickers hardness of 750 or greater, and a porosity of 2% or less by volume, preferably 0.5% or less, when the hardfacing layer is formed from an HVOF thermal spray process. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 shows a phase mole fraction versus temperature diagram for alloy P82-X6 showing the mole fractions of the phases present in the alloy at various temperatures. [Diagram 2] FIG. 2 shows a phase mole fraction diagram versus temperature for alloy P76-X23 showing the mole fractions of the phases present in the alloy at various temperatures. [Diagram 3] FIG. 3 shows an SEM image of one embodiment of alloy P82-X6, which includes a hard phase, a hypereutectic hard phase, and a matrix. [Figure 4] FIG. 4 shows an optical microscope image of P82-X6 laser welded from gas atomized powder in Example 1, parameter set 1. [Diagram 5] FIG. 5 shows SEM images of the gas atomized powder 501 and the resulting coating 502 of the P76-X24 alloy in Example 2. [Figure 6] FIG. 6 shows SEM images of HVOF coatings deposited from the agglomerated and sintered powder of WC / Cr3C2+Ni alloy in Example 3, specifically a mixture of 80 wt. % WC / Cr3C2 (50 / 50 vol.%) mixed with 20 wt. % Monel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Embodiments of the present disclosure include, but are not limited to, hardfacing / hardbanding materials, alloy or powder compositions used to make such hardfacing / hardbanding materials, methods of forming the hardfacing / hardbanding materials, and parts or substrates incorporating or protected by these hardfacing / hardbanding materials.
[0031] In certain applications, it may be advantageous to form a metal layer that is highly resistant to abrasive and corrosive wear and less susceptible to corrosion. Disclosed herein are embodiments of nickel-based alloys that have been developed to provide abrasive and corrosion resistance. Industries that may benefit from combined corrosion and abrasive resistance include marine applications, coatings in the power industry, oil and gas applications, and coatings for glass production.
[0032] In some embodiments, the alloys disclosed herein can be engineered to form microstructures with similar matrix chemistries to some known alloys, such as Inconel® and Hastelloy®, while also including additional elements to improve performance. For example, carbides can be added to the matrix of the material. In particular, improved corrosion resistance and improved wear resistance can be achieved.
[0033] It must be understood that in the complex alloy space, it is not possible to simply remove an element or substitute another and achieve equivalent results.
[0034] In some embodiments, nickel-based alloys as described herein may be suitable feedstocks for laser cladding hardfacing processes, including plasma transferred arc (PTA), high velocity laser cladding, and thermal spray processes, including high velocity oxygen fuel (HVOF) thermal spraying, although the disclosure is not so limited. Some embodiments include fabricating nickel-based alloys into cored wires for hardfacing processes, and methods for welding nickel-based wires and powders using wire-fed lasers and short wavelength lasers.
[0035] The term alloy may refer to the chemical composition of the powder used to form the metallic component, the powder itself, the chemical composition of the melt used to form the cast component, the melt itself, and the composition of the metallic component formed by heating, sintering, and / or deposition of the powder, including the composition of the metallic component after cooling. In some embodiments, the term alloy may refer to the chemical composition forming the disclosed powders, the powder itself, the feedstock itself, the wire, the wire with powder, the combined composition of the combination of wires, the composition of the metallic component formed by heating and / or deposition of the powder, or other techniques, and the metallic component.
[0036] In some embodiments, alloys made into solid or cored wires (powder-containing sheaths) for welding or for use as feedstock in other processes may be described herein by specific chemical compositions. For example, the wires may be used for thermal spraying. Additionally, the compositions disclosed below may be for a single wire or a combination of multiple wires (such as 2, 3, 4, or 5 wires).
[0037] In some embodiments, the alloy can be applied by a thermal spray process to form a thermal spray coating, such as an HVOF alloy. In some embodiments, the alloy can be applied as a weld build-up layer. In some embodiments, the alloy can be applied as a thermal spray layer or as a weld build-up layer, for example, having two uses.
[0038] [Metal alloy composition] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: B: 0 to 4 (or about 0 to about 4); C: 0 to 9.1 (or about 0 to about 9.1); Cr: 0 to 60.9 (or about 0 to about 60.9); Cu: 0 to 31 (or about 0 to about 31); Fe: 0 to 4.14 (or about 0 to about 4.14); Mn: 0 to 1.08 (or about 0 to about 1.08); Mo: 0 to 10.5 (or about 0 to about 10.5); Nb: 0 to 27 (or about 0 to about 27); Si: 0 to 1 (or about 0 to about 1); Ti: 0 to 24 (or about 0 to about 24); and W: 0 to 12 (or about 0 to about 12).
[0039] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 0.5 to 2 (or about 0.5 to about 2); Cr: 10-30 (or about 10-about 30); Mo: 5 to 20 (or about 5 to about 20); and It may contain Nb+Ti:2 to 10 (or about 2 to about 10).
[0040] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 0.8 to 1.6 (or about 0.8 to about 1.6); Cr: 14-26 (or about 14 to about 26); Mo: 8 to 16 (or about 8 to about 16); and It may contain Nb+Ti:2 to 10 (or about 2 to about 10).
[0041] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 0.84 to 1.56 (or about 0.84 to about 1.56); Cr: 14-26 (or about 14 to about 26); Mo: 8.4 to 15.6 (or about 8.4 to about 15.6); and Nb+Ti: 4.2 to 8.5 (or about 4.2 to about 8.5).
[0042] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 0.84 to 1.56 (or about 0.84 to about 1.56); Cr: 14-26 (or about 14 to about 26); Mo: 8.4 to 15.6 (or about 8.4 to about 15.6); Nb: 4.2 to 7.8 (or about 4.2 to about 7.8); and Ti: 0.35 to 0.65 (or about 0.35 to about 0.65).
[0043] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 1.08 to 1.32 (or about 1.08 to about 1.32); Cr: 13-22 (or about 13 to about 22); Mo: 10.8 to 13.2 (or about 10.8 to about 13.2); and Nb: 5.4 to 6.6 (or about 5.4 to about 6.6).
[0044] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 0.5 to 2 (or about 0.5 to about 2); Cr: 10-30 (or about 10-about 30); Mo: 5.81 to 18.2 (or about 5.81 to about 18.2); and Nb+Ti: 2.38 to 10 (or about 2.38 to about 10).
[0045] In some embodiments, products, such as ingredient compositions as disclosed herein, may include one of the following, in weight percent: C: 0.5, Cr: 24.8, Mo: 9.8, Ni: balance (or C: approx. 0.5, Cr: approx. 24.8, Mo: approx. 9.8, Ni: balance); C: 0.35-0.65, Cr: 17.3-32.3, Mo: 6.8-12.7, Ni: balance (or C: about 0.35-about 0.65, Cr: about 17.3-about 32.3, Mo: about 6.8-about 12.7, Ni: balance); C: 0.45-0.55, Cr: 22.3-27.3, Mo: 8.8-10.8, Ni: balance (or C: about 0.45-about 0.55, Cr: about 22.3-about 27.3, Mo: about 8.8-about 10.8, Ni: balance); C: 0.8, Cr: 25, Mo: 14, Ni: balance (or C: about 0.8, Cr: about 25, Mo: about 14, Ni: balance); C: 0.56-1.04, Cr: 17.5-32.5, Mo: 9.8-18.2, Ni: balance (or C: about 0.56-about 1.04, Cr: about 17.5-about 32.5, Mo: about 9.8-about 18.2, Ni: balance); C: 0.7-0.9, Cr: 22.5-27.5, Mo: 12.6-15.4, Ni: balance (or C: about 0.7-about 0.9, Cr: about 22.5-about 27.5, Mo: about 12.6-about 15.4, Ni: balance); C: 1.2, Cr: 24, Mo: 14, Ni: balance (or C: approx. 1.2, Cr: approx. 24, Mo: approx. 14, Ni: balance); C: 0.84-1.56, Cr: 16.8-31.2, Mo: 9.8-18.2, Ni: balance (or C: about 0.84-about 1.56, Cr: about 16.8-about 31.2, Mo: about 9.8-about 18.2, Ni: balance); C: 1.08-1.32, Cr: 21.6-26.4, Mo: 12.6-15.4, Ni: balance (or C: about 1.08-about 1.32, Cr: about 21.6-about 26.4, Mo: about 12.6-about 15.4, Ni: balance); C: 1.2, Cr: 20, Mo: 12, Nb: 6, Ti: 0.5, Ni: balance (or C: about 1.2, Cr: about 20, Mo: about 12, Nb: about 6, Ti: about 0.5, Ni: balance); C: 0.84 to 1.56, Cr: 14 to 26, Mo: 8.4 to 15.6, Nb: 4.2 to 7.8, Ti: 0.35 to 0.65, Ni: balance (or C: about 0.84 to about 1.56, Cr: about 14 to about 26, Mo: about 8.4 to about 15.6, Nb: about 4.2 to about 7.8, Ti: about 0.35 to about 0.65, Ni: balance); C: 1.08-1.32, Cr: 18-22, Mo: 10.8-13.2, Nb: 5.4-6.6, Ti: 0.45-0.55, Ni: balance (or C: about 1.08-about 1.32, Cr: about 18-about 22, Mo: about 10.8-about 13.2, Nb: about 5.4-about 6.6, Ti: about 0.45-about 0.55, Ni: balance); C: 1.6, Cr: 18, Mo: 14, Nb: 6, Ni: balance (or C: about 1.6, Cr: about 18, Mo: about 14, Nb: about 6, Ni: balance); C: 1.12 to 2.08, Cr: 12.6 to 23.4, Mo: 9.8 to 18.2, Nb: 4.2 to 7.8, Ni: balance (or C: about 1.12 to about 2.08, Cr: about 12.6 to about 23.4, Mo: about 9.8 to about 18.2, Nb: about 4.2 to about 7.8, Ni: balance); C: 1.44~1.76, Cr: 16.2~19.8, Mo: 12.6~15.4, Nb: 5.4~6.6, Ni: balance (or C: about 1.44~about 1.76, Cr: about 16.2~about 19.8, Mo: about 12.6~about 15.4, Nb: about 5.4~about 6.6, Ni: balance).
[0046] In some embodiments, the product, such as the composition of the feedstock as disclosed herein, comprises Ni and, in weight percent: C: 1.4, Cr: 16, Fe: 1.0, Mo: 10, Nb: 5, Ti: 3.8 (or C: about 1.4, Cr: about 16, Fe: about 1.0, Mo: about 10, Nb: about 5, Ti: about 3.8); B: 3.5, Cu: 14 (or B: about 3.5, Cu: about 14); B: 2.45 to 4.55 (or about 2.45 to about 4.55), Cu: 9.8 to 18.2 (or about 9.8 to about 18.2); B: 3.15 to 3.85 (or about 3.15 to about 3.85), Cu: 12.6 to 15.4 (or about 12.6 to about 15.4); B: 4.0, Cr: 10, Cu: 16 (or B: about 4.0, Cr: about 10, Cu: about 16); B: 2.8 to 5.2 (or about 2.8 to about 5.2), Cr: 7 to 13 (or about 7 to about 13), Cu: 11.2 to 20.8 (or about 11.2 to about 20.8); B: 3.6 to 4.4 (or about 3.6 to about 4.4), Cr: 9 to 11 (or about 9 to about 11), Cu: 14.4 to 17.6 (or about 14.4 to about 17.6); or It may include C: 1.2, Cr: 20, Mo: 12, Nb: 6, Ti: 0.5 (or C: about 1.2, Cr: about 20, Mo: about 12, Nb: about 6, Ti: about 0.5).
[0047] In some embodiments, the product, such as the composition of ingredients as disclosed herein, comprises, in weight percent, an agglomerated and sintered 75~85%WC+15~25%Monel; 65~75%WC+25~35%Monel; 60~75%WC+25~40%Monel; 75~85%Cr3C2+15~25%Monel; 65~75%Cr3C2+25~35%Monel; 60~75%Cr3C2+25~40%Monel; 60~85%WC+15~40%Ni30Cu; 60~85%Cr3C2+15~40%Ni30Cu; 75~85%(50 / 50vol%)WC / Cr3C2+15~25%Monel; 75~85%(50 / 50vol%)WC / Cr3C2+25~35%Monel; 75~85%WC / Cr3C2+15~25%Monel; 75~85%WC / Cr3C2+25~35%Monel; or It may contain a mixture of 60-90% hard phase + 10-40% Monel alloy.
[0048] In the above, the hard phase is one or more of tungsten carbide (WC) and / or chromium carbide (Cr3C2). Monel® is a nickel copper alloy with a target composition of Ni balance 30 wt% Cu with typical chemical tolerances of 20-40 wt% Cu or more preferably 28-34 wt% Cu with known impurities including but not limited to C, Mn, S, Si, and Fe. Monel does not contain any carbides, and therefore embodiments of the present disclosure include carbides such as tungsten carbide and / or chromium carbide. Tungsten carbide is generally represented by the formula W: balance 4-8 wt% C. In some embodiments, tungsten carbide can be generally represented by the formula W: balance 1.5 wt% C.
[0049] In some embodiments having 60-85% WC+Ni30Cu, the product has, in weight percent: Ni: 10.5 to 28 (or about 10.5 to about 28); Cu: 4.5 to 12 (or about 4.5 to about 12); C: 3.66 to 5.2 (or about 3.66 to about 5.2); W: 56.34 to 79.82 (or approximately 56.34 to approximately 79.82).
[0050] In some embodiments having 60-85% Cr3C2+Ni30Cu, the product has, in weight percent: Ni: 10.5 to 28 (or about 10.5 to about 28); Cu: 4.5 to 12 (or about 4.5 to about 12); C: 7.92 to 11.2 (or about 7.92 to about 11.2); W: 52.1 to 73.78 (or about 52.1 to about 73.79).
[0051] Thus, the above feedstock description shows that tungsten carbide, a known alloy of simple formula (as represented by the simple formula Ni30Cu in the given ratios), was mechanically mixed with Monel. During this entire process, many particles became stuck together to form new "agglomerated" particles. In each case, the agglomerated particles were of the ratios described.
[0052] Table 1 lists a number of experimental alloys along with their compositions in weight percent. [Table 1]
[0053] In some embodiments, the P76 alloy may be a thermal spray alloy and the P82 alloy may be a weld overlay alloy (such as PTA or laser). However, the disclosure is not so limited. For example, any of the compositions as disclosed herein may be suitable for hardfacing processes such as plasma transferred arc (PTA), laser cladding hardfacing processes, including high velocity laser cladding, and thermal spray processes such as high velocity oxygen fuel (HVOF) thermal spraying.
[0054] In Table 1, all values can also be referred to as "about" the stated value. For example, in P82-X1, Ni is 59 (or about 59).
[0055] In some embodiments, the disclosed compositions can be wires / powder, coatings or other metallic members, or both.
[0056] The disclosed alloys may include up to 100% by weight of the above-listed elemental components in total. In some embodiments, the alloys may include, be limited to, or consist essentially of the above-listed elements. In some embodiments, the alloys may include impurities in amounts of 2% (or about 2%) or less, 1% (or about 1%) or less, 0.5% (or about 0.5%) or less, 0.1% (or about 0.1%) or less, or 0.01% (or about 0.01%) or less, or any range between any of these values. Impurities may be understood as elements or compositions that may be included in the alloy as they are included in the raw material components by being introduced during the manufacturing process.
[0057] Additionally, the Ni content specified in all of the compositions described in the preceding paragraphs may be the balance of the composition, or, where Ni is provided as the balance, the balance of the composition may include Ni and other elements, in some embodiments, the balance may consist essentially of Ni and include incidental impurities.
[0058] [Thermodynamic conditions] In some embodiments, an alloy can be characterized by its equilibrium thermodynamic conditions. In some embodiments, an alloy can be characterized as satisfying some of the described thermodynamic conditions. In some embodiments, an alloy can be characterized as satisfying all of the described thermodynamic conditions.
[0059] The first thermodynamic condition relates to the total concentration of ultrahard particles in the microstructure. As the mole fraction of ultrahard particles increases, the bulk hardness of the alloy may increase, and therefore the wear resistance may also increase, which may be advantageous for hardfacing applications. For the purposes of this disclosure, ultrahard particles may be defined as phases that exhibit a hardness of 1000 Vickers or greater (or about 1000 Vickers or greater). The total concentration of ultrahard particles may be defined as the total mole % of all phases that meet or exceed a hardness of 1000 Vickers (or about 1000 Vickers) and are thermodynamically stable at 1500K (or about 1500K) in the alloy.
[0060] In some embodiments, the ultra-hard particle fraction is 3 mol% or more (or about 3 mol% or more), 4 mol% or more (or about 4 mol% or more), 5 mol% or more (or about 5 mol% or more), 8 mol% or more (or about 8 mol% or more), 10 mol% or more (or about 10 mol% or more), 12 mol% or more (or about 12 mol% or more), or 15 mol% or more (or about 15 mol% or more), 20 mol% or more (or about 20 mol% or more), 30 mol% or more (or about 30 mol% or more), 40 mol% or more (or about 40 mol% or more), 50 mol% or more (or about 50 mol% or more), 60 mol% or more (or about 60 mol% or more), or any range between any of these values.
[0061] In some embodiments, the ultra-hard particle fraction can vary depending on the intended alloy processing. For example, in thermal spray alloys, the hard particle fraction can be 40-60 mole % (or about 40 to about 60 mole %). In alloys used for welding by laser, plasma transferred arc, or other wire welding procedures, the hard particle phase fraction can be 15-30 mole % (or about 15 to about 30 mole %).
[0062] The second thermodynamic condition relates to the amount of hypereutectic hard phases that form in the alloy. Hypereutectic hard phases are hard phases that begin to form at temperatures above the eutectic point of the alloy. The eutectic point of these alloys is the temperature at which the FCC matrix begins to form.
[0063] In some embodiments, the hypereutectic hard phases comprise a total of 40 molar% or more (or about 40% or more), 45 molar% or more (or about 45% or more), 50 molar% or more (or about 50% or more), 60 molar% or more (or about 60% or more), 70 molar% or more (or about 70% or more), 75 molar% or more (or about 75% or more), or 80 molar% or more (or about 80% or more), or any range between any of these values, of the total hard phases present in the alloy.
[0064] The third thermodynamic condition relates to the corrosion resistance of the alloy. The corrosion resistance of nickel-based alloys can be increased when a higher weight percentage of chromium and / or molybdenum is present in the FCC matrix. This third thermodynamic condition evaluates the total weight percentage of chromium and molybdenum in the FCC matrix at (or about) 1500K.
[0065] In some embodiments, the total weight percent of chromium and molybdenum in the base material is 15 wt.% or more (or about 15 wt.% or more), 18 wt.% or more (or about 18 wt.% or more), 20 wt.% or more (or about 20 wt.% or more), 23 wt.% or more (or about 23 wt.% or more), 25 wt.% or more (or about 25 wt.% or more), 27 wt.% or more (or about 27 wt.% or more), or 30 wt.% or more (or about 30 wt.% or more), or any range between any of these values.
[0066] The fourth thermodynamic condition relates to the base metal chemistry of the alloy. In some embodiments, it may be beneficial to keep the base metal chemistry similar to that of a known alloy, such as, for example, Inconel 622, Inconel 625, Inconel 686, Hastelloy C276, Hastelloy X, or Monel 400. In some embodiments, to keep the base metal chemistry similar to that of the known alloy, the base metal chemistry of the alloy at 1300 K was compared to that of the known alloy. Such a comparison is called base metal closeness. In general, such superalloys can be represented by the composition in weight percent: Ni: balance, Cr: 15-25, Mo: 8-20. Inconel622 Cr: 20~22.5, Mo: 12.5~14.5, Fe: 2~6, W: 2.5~3.5, Ni: balance Inconel625 Cr: 20~23, Mo: 8~10, Nb+Ta: 3.15~4.15, Ni: balance Inconel686 Cr: 19-23, Mo: 15-17, W: 3-4.4, Ni: balance HastelloyC276 Cr:16, Mo:16, Fe:5, W:4, Ni:Remaining HastelloyX Cr:22, Fe:18, Mo:9, Ni:Remaining Monel Cr: 28~34, Ni: remaining amount
[0067] In some embodiments, the parent material similarity is 50% (or about 50%) or more, 55% (or about 55%) or more, 60% (or about 60%) or more, 70% (or about 70%) or more, 80% (or about 80%) or more, 85% (or about 85%) or more, 90% (or about 90%) or more of any of the above known alloys. Parent material similarity can be determined by a number of methods, such as energy dispersive spectroscopy (EDS).
[0068] The following formula can be used to calculate the similarity or closeness of a model alloy base material to an alloy of known corrosion resistance. A value of 100% means exact agreement between the compared elements.
number
[0069] A fifth thermodynamic condition relates to the liquidus temperature of the alloy, which can be used to determine whether the alloy is suitable for the gas atomization manufacturing process. The liquidus temperature is the lowest temperature at which the alloy is still 100% liquid. Generally, a lower liquidus temperature corresponds to increased stability of the gas atomization process. In some embodiments, the liquidus temperature of the alloy can be 1850K (or about 1850K) or less. In some embodiments, the liquidus temperature of the alloy can be 1600K (or about 1600K) or less. In some embodiments, the liquidus temperature of the alloy can be 1450K (or about 1450K) or less.
[0070] The thermodynamic behavior of alloy P82-X6 is shown in FIG. 1. The diagram shows the material precipitating hypereutectic FCC carbides 101 in a nickel matrix 103, which is greater than 5% at 1500K. 101 shows the FCC carbide fraction as a function of temperature, forming a separate hypereutectic phase. 102 refers to the total hard phase content at 1300K, which includes FCC carbides in addition to M6C carbides. Thus, the hypereutectic hard phase is greater than 50% of the total hard phase of the alloy. 103 refers to the matrix of the alloy, which is a FCC_L12 nickel matrix. The matrix closeness of alloy 103 is greater than 60% when compared to Inconel 625.
[0071] M6C type carbides also precipitate at lower temperatures and constitute approximately 15 mole % of the total carbide content at 1300K (12.6% FCC carbides, 2.4% M6C carbides). The FCC carbides represent the segregated carbides in the alloy and constitute the majority (>50%) of the total carbides in the alloy. The arrows specifically point to the extraction of the FCC_L12 matrix composition for insertion into the matrix closeness equation. As shown in this example, while the volume fraction of all hard phases is greater than 5 mole %, more than 50% of the carbide fraction forms as a hypereutectic phase known to form segregated morphologies, with the remaining FCC_L12 matrix phase having a closeness to Inconel 625 of greater than 60%.
[0072] In this calculation, the chemical composition of the FCC_L12 matrix phase is extracted, although it is not shown in Figure 1. The matrix chemical composition is 18 wt% Cr, 1 wt% Fe, 9 wt% Mo, and 1 wt% Ti, with the balance being Ni. It can be seen that the matrix chemical composition of P82-X6 is completely different from the bulk chemical composition of P82-X6. P82-X6 is designed to have similar corrosion performance to Inconel625, and the matrix similarity to Inconel625 is 87%.
[0073] The thermodynamic behavior of alloy P76-X23 is shown in FIG. 2. The diagram shows the material precipitating eutectic Ni3B203 in a nickel matrix 201. 201 shows the liquidus temperature of the alloy, which in the preferred embodiment is below 1850K. 202 shows the mole fraction of the hard phase in the alloy, in this case nickel boride (Ni3B) at 1200K, which is greater than 5 mole %. 203 shows the matrix phase fraction where the matrix chemistry is extracted at 1200K, and where the matrix closeness is greater than 60% to Monel. The liquidus temperature of the alloy is 1400K, which makes the material very suitable for gas atomization. Ni3B is the hard phase in this example, and is present at a mole fraction of 66% at 1300K. The matrix chemistry is 33% Cu by weight, the balance being nickel. It can be seen that the base metal chemistry of P76-X23 is completely different from the bulk chemistry of P76-X23. P76-X23 is designed to have similar corrosion performance to Monel 400, and the base metal similarity of P76-X23 to Monel 400 is 100%.
[0074] [Microstructure conditions] In some embodiments, the alloys can be described by their microstructural conditions. In some embodiments, the alloys can be characterized as meeting some of the described microstructural conditions. In some embodiments, the alloys can be characterized as meeting all of the described microstructural conditions.
[0075] The first microstructural condition relates to the total measured volume fraction of ultra-hard particles. For purposes of this disclosure, ultra-hard particles may be defined as phases that exhibit a hardness of 1000 Vickers or greater (or about 1000 Vickers or greater). The total concentration of ultra-hard particles may be defined as the total mole percent of all phases that meet or exceed a hardness of 1000 Vickers (or about 1000 Vickers) and are thermodynamically stable at 1500 K (or about 1500 K) in the alloy. In some embodiments, the alloy has at least 3% by volume (or at least about 3% by volume), at least 4% by volume (or at least about 4% by volume), at least 5% by volume (or at least about 5% by volume), at least 8% by volume (or at least about 8% by volume), at least 10% by volume (or at least about 10% by volume), at least 12% by volume (or at least about 12% by volume), or at least 15% by volume (or at least about 15% by volume) of super-hard particles, at least 20% by volume (or at least about 20% by volume) of super-hard particles, at least 30% by volume (or at least about 30% by volume) of super-hard particles, at least 40% by volume (or at least about 40% by volume) of super-hard particles, at least 50% by volume (or at least about 50% by volume) of super-hard particles, or any range between any of these values.
[0076] In some embodiments, the ultra-hard particle fraction can vary depending on the intended alloy processing. For example, in a thermal spray alloy, the hard particle fraction can be 40-60% by volume (or about 40 to about 60% by volume). In an alloy used for welding by laser, plasma transferred arc, or other wire welding procedures, the hard particle phase fraction can be 15-30% by volume (or about 15 to about 30% by volume).
[0077] The second microstructural condition relates to the fraction of hypereutectic separated hard phases in the alloy. As used herein, separation can mean that a particular separated phase (such as a spherical or partially spherical particle) is not connected to other hard phases. For example, a separated phase can be 100% surrounded by the matrix phase. This can be contrasted with rod-like phases, which can form long needles that act as low-toughness "bridges" that initiate cracks across the microstructure.
[0078] To reduce the susceptibility of the alloy to cracking, it may be beneficial to form a separate hypereutectic phase rather than a continuous grain boundary phase. In some embodiments, the separate hypereutectic hard phases total 40% by volume (or about 40%) or more, 45% by volume (or about 45%) or more, 50% by volume (or about 50%) or more, 60% by volume (or about 60%) or more, 70% by volume (or about 70%) or more, 75% by volume (or about 75%) or more, or 80% by volume (or about 80%) or more, or any range between any of these values, of the total hard phase fraction present in the alloy.
[0079] The third microstructural condition relates to increasing corrosion resistance in the alloy. To increase corrosion resistance in nickel-based alloys, it may be beneficial to have a higher total weight percent of chromium and molybdenum in the matrix. Energy dispersive spectroscopy (EDS) was used to measure the total weight percent of chromium and molybdenum in the matrix. In some embodiments, the total chromium and molybdenum content in the matrix may be 15 wt% or more (or about 15 wt% or more), 18 wt% or more (or about 18 wt% or more), 20 wt% or more (or about 20 wt% or more), 23 wt% or more (or about 23 wt% or more), 25 wt% or more (or about 25 wt% or more), 27 wt% or more (or about 27 wt% or more), or 30 wt% or more (or about 30 wt% or more), or any range between any of these values.
[0080] The fourth microstructural condition relates to the matrix closeness of the alloy compared to that of a known alloy, such as, for example, Inconel 625, Inconel 686, or Monel. Energy dispersive spectroscopy (EDS) was used to measure the matrix chemical composition of the alloy. In some embodiments, the matrix closeness is 50% (or about 50%) or more, 55% (or about 55%) or more, 60% (or about 60%) or more, 70% (or about 70%) or more, 80% (or about 80%) or more, 85% (or about 85%) or more, or 90% (or about 90%) or more, or any range between any of these values, of the known alloy.
[0081] The matrix approximation is similar to that described in the thermodynamic terms section and is calculated in this case. The difference between "matrix chemistry" and "matrix approximation" is that the chemistry is the actual value of Cr, Mo, or other elements found in solid solution in the nickel matrix. Approximation is a percentage value used as a quantitative measure of how closely the nickel matrix of a design alloy matches the chemistry of known alloys that have good corrosion resistance. To be clear, known alloys such as Inconel are single phase alloys, so the alloy composition is effectively the matrix composition, with all alloying elements found in solid solution. This is not the case with the alloys described herein, which precipitate hard phases for wear resistance.
[0082] Figure 3 shows SEM images of the microstructure of P82-X6 as prepared by PTA welding. In this case, the alloy was prepared as a powder mixture for the experiment. 301 shows segregated niobium carbide precipitates with a volume fraction of more than 5% at 1500K, 302 shows a hypereutectic hard phase with more than 50% of the total hard phase in the alloy, and 303 shows a matrix with a matrix closeness of more than 60% when compared to Inconel 625. The carbide precipitates form a combination of segregated (larger size) and eutectic (smaller size) forms that both contribute to the total hard phase content. In this example, the segregated hard phase is more than 50% of the total carbide fraction by volume.
[0083] [Performance Conditions] In some embodiments, the hardfacing layer is created by a weld build-up process, including but not limited to PTA cladding or laser cladding.
[0084] In some embodiments, the alloy may have a number of advantageous performance characteristics. In some embodiments, it may be advantageous for the alloy to have one or more of: 1) high abrasion resistance, 2) minimal or no cracking when welded by laser cladding processes or other welding methods, and 3) high corrosion resistance. The abrasion resistance of the hardfacing alloy may be quantified using the ASTM G65A dry sand abrasion test. The crack resistance of the material may be quantified using a dye penetration test on the alloy. The corrosion resistance of the alloy may be quantified using the ASTM G48, G59, and G61 tests. All of the above-mentioned ASTM tests are incorporated herein by reference in their entirety.
[0085] In some embodiments, the hardfacing layer is 250 mm 3 Less than (or about 250 mm 3 Less than 100mm 3 Less than (or about 100 mm 3 Less than 30mm 3 Less than (or about 30 mm 3 Less than 20mm 3 Less than (or about 20 mm 3 The material may have an ASTM G65A abrasion loss of less than 100%.
[0086] In some embodiments, the hardfacing layer may develop 5 cracks per square inch, 4 cracks per square inch, 3 cracks per square inch, 2 cracks per square inch, 1 crack per square inch, or 0 cracks per square inch of coating, or any range between any of these values. In some embodiments, the cracks are lines of surface that are cracked without breaking into separate pieces.
[0087] In some embodiments, the hardfacing layer can have a corrosion resistance of 50% (or about 50%) or more, 55% (or about 55%) or more, 60% (or about 60%) or more, 70% (or about 70%) or more, 80% (or about 80%) or more, 85% (or about 85%) or more, 90% (or about 90%) or more, 95% (or about 95%) or more, 98% (or about 98%) or more, 99% (or about 99%) or more, or 99.5% (or about 99.5%) or more, or any range between any of these values, of known alloys.
[0088] Corrosion resistance is complex and may depend on the corrosive medium used. Preferably, the corrosion rates of the disclosed alloy embodiments may be approximately equal to the corrosion rates of the alloys they are intended to replicate. For example, if Inconel 625 has a corrosion rate of 1 mpy (mils per year) in a particular corrosive medium, P82-X6 may have a corrosion resistance of 1.25 mpy or less to obtain 80% corrosion resistance. Corrosion resistance is defined as 1 / corrosion rate for purposes of this disclosure.
[0089] In some embodiments, the alloy can have a corrosion rate of 1 mpy or less (or about 1 mpy or less) in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the alloy can have a corrosion rate of 0.6 mpy or less (or about 0.6 mpy or less) in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the alloy can have a corrosion rate of 0.4 mpy or less (or about 0.4 mpy or less) in a 28% CaCl2 electrolyte, pH=9.5 environment.
[0090] In some embodiments, the alloy may have a corrosion resistance of less than (or less than about) 0.1 mpy in 3.5% sodium chloride solution for 16 hours according to G-59 / G-61.In some embodiments, the alloy may have a corrosion resistance of less than (or less than about) 0.08 mpy in 3.5% sodium chloride solution for 16 hours according to G-59 / G-61.
[0091] In some embodiments, the hardfacing layer is created by a thermal spray process, including but not limited to, high velocity fuel (HVOF) thermal spraying.
[0092] In some embodiments, the hardness of the coating can be greater than or equal to 650 (or about 650) Vickers. In some embodiments, the hardness of the thermal spray process can be greater than or equal to 700 (or about 700) Vickers. In some embodiments, the hardness of the thermal spray process can be greater than or equal to 900 (or about 900) Vickers.
[0093] In some embodiments, the adhesion of the thermal spray coating can be 7,500 (or about 7,500) psi or greater. In some embodiments, the adhesion of the thermal spray coating can be 8,500 (or about 8,500) psi or greater. In some embodiments, the adhesion of the thermal spray coating can be 9,500 (or about 9,500) psi or greater. EXAMPLES
[0094] [Example 1: PTA welding of P82-X6] Alloy P82-X6 was gas atomized into a powder with a 53-150 μm particle size distribution suitable for PTA and / or laser cladding. The alloy was laser clad using two parameter sets: 1) 1.8 kW laser power and 20 L / min flow rate, and 2) 2.2 kW laser power and 14 L / min flow rate. In both cases, the coating showed finely separated niobium / titanium carbide precipitates 401 in the nickel matrix 402 as intended, as shown in FIG. 4. The 300 gram force Vickers hardness of the laser clad was 435 and 348 for parameter sets 1 and 2, respectively. ASTM G65 testing yielded a Vickers hardness of 1.58 g (209 mm) for parameter sets 1 and 2, respectively. 3 ) loss and 1.65g (200mm 3 ) loss.
[0095] [Example 2: HVOF spraying of P76-X23 and P76-X24] Alloys P76-X23 and P76-X24 were gas atomized into powders with a 15-45 μm particle size distribution suitable for HVOF thermal spray processing. Both powders produce extremely fine-scale morphologies in which nickel matrix and nickel boride phases are believed to coexist as predicted by computational modeling, but are very difficult to distinguish and quantitatively measure.
[0096] As shown in FIG. 5, 501 is the gas atomized powder and 502 is the resulting powder coating, in addition to the matrix and Ni boride phases 504 (e.g., the eutectic nickel / nickel boride structure of the gas atomized powder), the P76-X24 alloy also forms chromium boride precipitates 503 as predicted by the model as finely separated particles.
[0097] 505 indicates an area of primary nickel / nickel boride eutectic structure in the HVOF sprayed coating, and 506 indicates an area of the coating containing many chromium boride precipitates.
[0098] Both alloys were HVOF sprayed to a coating thickness of approximately 200-300 μm to produce dense coatings. The Vickers hardness at 300 grams force of the coatings was 693 and 726 for P76-X23 and P76-X24, respectively. Adhesion testing of P76-X23 resulted in adhesion failure up to 9,999 psi, while P76-X24 showed 75% adhesion and 25% adhesion failure in two tests reaching 9,576 and 9,999 psi. ASTM G65A (converted from ASTM G65B testing) testing showed that P76-X24 had a failure rate of 87 mm. 3 The ASTM G65A test uses 6,000 rpm, while Method B uses 2,000 rpm and is typically used for thin film coatings such as thermal spray coatings.
[0099] P76-X24 was tested in 28% CaCl2 electrolyte, pH=9.5, with a measured corrosion rate of 0.4mpy. In comparison, cracked hard chrome exhibits a rate of 1.06mpy in a similar environment. Hard Cr is used as a suitable coating for a variety of applications requiring both corrosion and abrasion resistance. In some embodiments, the alloy in the form of an HVOF coating provides a corrosion rate of 1mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the alloy in the form of an HVOF coating can provide a corrosion rate of 0.6mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the alloy in the form of an HVOF coating can provide a corrosion rate of 0.4mpy or less in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the alloy in the form of an HVOF coating provides an impermeable coating in an ECP (electrochemical potential) test.
[0100] [Example 3: HVOF spraying of WC / Cr3C2, Ni alloy matrix mixture] A mixture of 80 wt% WC / Cr3C2 (50 / 50 volume%) mixed with 20 wt% Monel was agglomerated to 15-45 μm, suitable for thermal spray processing, and sintered. The HVOF coating produced a dense coating with a 300 gram Vickers hardness of 946 and a measured porosity of 0.43%, as shown in Figure 6. The HVOF coating had a thickness of approximately 12 mm per ASTM G65A. 3 6 shows SEM images of the agglomerated and sintered powder of WC / Cr3C2+Ni alloy in Example 3, specifically a mixture of 80 wt% WC / Cr3C2 (50 / 50 vol%) mixed with 20 wt% Monel.
[0101] Example 4: Welding study of P82-X13, 14, 15, 18, 19 in comparison with Inconel 625. Welding studies were performed evaluating several alloys with various carbide contents and morphologies in comparison to Inconel 625. All alloys in the study were used to form a matrix similar to Inconel 625, which is quantified by matrix closeness, with 100% being equivalent to a matrix that closely resembles the bulk composition of Inconel 625. All alloys were laser welded in three overlapping layers to test for crack resistance. Similarly, two-layer welds of each alloy were created by plasma transferred arc welding to test for cracking and other properties. [Table 2]
[0102] P82-X18 represents an embodiment of this disclosure that performs well at the conclusion of this study. P82-X18 is significantly harder than Inconel 625 in both PTA and laser processing. The increased hardness did not result in any apparent cracking in the laser or PTA cladded samples. P82-X18 shows improved abrasion resistance when compared to Inconel 625 in both processing. The general trend of increasing hardness is similar for all tested alloys, as shown in Table 3. However, surprisingly, increased hardness does not result in increased abrasion resistance in all cases. P82-X13, P82-X14, and P82-X15, although all harder and containing carbides, showed wear rates greater than Inconel 625. This result indicates the discovery of favorable carbide morphology when compared to the total carbide fraction and alloy hardness.
[0103] Alloy P82-X18 meets the thermodynamic, microstructural, and performance criteria of this disclosure. P82-X18 is predicted to form 8.1 mol % segregated carbides and actually forms 8-12% segregated carbides in the industrially relevant welding processes studied. This alloy is also predicted to form 9.9 mol % intergranular hard phase and actually forms up to 10 vol % intergranular hard phase. The segregated carbide content is greater than 40% of the total carbide content in the alloy. This increase in segregated carbide fraction ratio improves wear resistance beyond that which would be expected from the total carbide fraction alone. [Table 3] [Table 4]
[0104] The base metal of P82-X18 was measured by energy dispersive spectroscopy to give Cr: 19-20 wt%, Mo: 10-12 wt%, Ni: balance. Thus, the base metal composition is very similar and to some extent overlaps with the typical Inconel 625 manufacturing range of Cr: 20-23, Mo: 8-10, Nb+Ta: 3.15-4.15, Ni: balance. P82-X18 was tested in the G-48 ferric chloride immersion test for 24 hours and, like Inconel 625, showed no corrosion. P82-X18 was corrosion tested in a 3.5% sodium chloride solution for 16 hours according to the G-59 / G-61 ASTM standard and a corrosion rate of 0.075-0.078 mpy (mils per year) was measured.
[0105] In some embodiments, the corrosion rate of the material measured in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61 is less than 0.1 mpy. In some embodiments, the corrosion rate of the material measured in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61 is less than 0.08 mpy.
[0106] In some embodiments, the alloys disclosed herein, such as P82-X18, can be used in place of nickel or other common materials as the metal component in carbide metal matrix composites (MMCs). A common example of an MMC type includes, by weight, 60% WC and 40% Ni. Utilizing P82-X18 in this example would result in an MMC type that is 60% WC and 40% P82-X18 by weight. A variety of carbide ratios and types can be used.
[0107] Example 5: HVOF spray study of P82-X18 P82-X18 was thermally sprayed using a hydrogen fuel HVOF process. The resulting coating had an adhesion strength of 10,000 psi, a Vickers hardness of 700 HV300, and an ASTM G65B mass loss of 0.856 (10.4.6 g / mm 3 The volume loss was
[0108] Example 6: HVOF spray study of 30% NiCu agglomerated and sintered materials. Two powders were produced by agglomeration and sintering process according to the formula 1) 65-75% WC / Cr3C2+25-35% NiCu alloy and formula 2) 65-75% Cr3C2+25-35% NiCu alloy. The first mixture is defined as 65-75% of the total volume fraction of the agglomerated and sintered particles is carbide, and the remaining part is NiCu metal alloy. The carbide content of the particles is itself composed of a combination of both carbide types, WC and Cr3C2. In some embodiments, the WC / Cr3C2 ratio is 0-100 by volume. In some embodiments, the WC / Cr3C2 ratio is about 0.33-3 by volume. In some embodiments, the WC / Cr3C2 ratio is about 0.25-5 by volume. In some embodiments, the WC / Cr3C2 ratio is about 0.67-1.5. The composition of the NiCu alloy is Cu: 20-40 wt %, preferably Cu: 25-35 wt %, more preferably Cu: 28-34 wt %, balance nickel, with other common impurities each less than 3 wt %.
[0109] Both powders were thermally sprayed by HVOF processing to form coatings which were tested. Coatings made from Powder 1 and Powder 2 exhibited corrosion rates of 0.15 mpy and 0.694 mpy, respectively, in a 28% CaCl2 electrolyte, pH=9.5 solution. Coatings made from Powder 1 and Powder 2 were impermeable as measured by ECP testing. Coatings made from Powder 1 and Powder 2 each exhibited corrosion rates of 11.3 mm per ASTM G65A. 3 and 16.2mm 3 The coatings made from Powder 1 and Powder 2 exhibited microhardness values of 816 HV300 and 677 HV300, respectively. The coatings made from both powders had adhesive strengths in excess of 12,500 psi.
[0110] [Application] The alloys described in this disclosure can be used in a variety of applications and industries. Some non-limiting examples of applications include surface mining applications, marine applications, power industry applications, oil and gas applications, and glass manufacturing applications.
[0111] Surface mining applications include the following components and coatings of: wear resistant sleeves and / or wear resistant hardfacings for slurry pipelines, mud pump components or mud pump component hardfacings including pump housings or impellers, feed chute components including chute blocks or chute block hardfacings, separation screens including but not limited to rotary breaker screens, banana screens, and shaker screens, autogenous and semi-autogenous grinding mill liners, excavation tools and excavation tool hardfacings, wear plates for bucket and dump truck liners, mining shovel heel blocks and heel block hardfacings, grader blades and grader blade hardfacings, stacker reclaimers, sizer crushers, general wear packages for mining components and other comminution components.
[0112] From the foregoing, it will be appreciated that an inventive nickel-base hardfacing alloy and method of use are disclosed. While certain components, techniques, and aspects have been described with a certain degree of detail, it will be apparent that many variations can be made in the specific designs, configurations, and methods described hereinabove without departing from the spirit and scope of the present disclosure.
[0113] Certain features that are described in this disclosure in the context of separate embodiments can also be implemented in combination in a single embodiment. Alternatively, various features that are described in the context of a single embodiment can also be implemented separately in multiple embodiments or in any suitable subcombination. Furthermore, although features may be described above as acting in certain combinations, one or more features in a described combination can, in some cases, be removed from the combination and the combination described as a subcombination or variation of the subcombination.
[0114] Also, although methods may be shown in the drawings or described in the specification in a particular order, such methods need not be performed in the particular order shown or in sequential order, and not all methods need to be performed, to achieve desired results. Other methods not shown or described can be incorporated into the illustrated methods and processes. By way of example, one or more additional methods can be performed before, after, simultaneously with, or between any of the described methods. Furthermore, methods can be rearranged or sequenced in other embodiments. Also, the separation of various system components in the above-described embodiments should not be understood as requiring such separation in all embodiments, and it should be understood that the described components and systems can generally be integrated together in a single product or packaged in multiple products. Moreover, other embodiments are within the scope of this disclosure.
[0115] Unless specifically stated or understood within the context in which it is used, conditional language such as "can," "could," "may," or "may" is generally intended to mean that a given embodiment includes or does not include certain features, components, and / or steps. As such, such conditional language is generally not intended to suggest that the features, components, and / or steps are in some way required for one or more embodiments.
[0116] Unless specifically stated, conjunctive language, such as "at least one of X, Y, and Z," is understood in the context in which it is commonly used to mean that an item, term, etc. can be either X, Y, or Z. Thus, such conjunctive language is not generally intended to suggest that a given embodiment requires the presence of at least one X, at least one Y, and at least one Z.
[0117] As used herein, degree language such as the terms "approximately," "about," "generally," and "substantially" refer to values, amounts, or characteristics that are close to the stated value, amount, or characteristic, yet perform the desired function or obtain the desired result. By way of example, the terms "approximately," "about," "generally," and "substantially" can refer to amounts that are 10% or less, 5% or less, 1% or less, 0.1% or less, 0.01% or less of the stated amount. When the stated amount is zero (e.g., none, none), the ranges mentioned above can be specific ranges, not within a specific percentage of a value. By way of example, 10% or less by weight / volume, 5% or less by weight / volume, 1% or less by weight / volume, 0.1% or less, 0.01% or less by weight / volume of the stated amount.
[0118] Any particular features, aspects, methods, properties, attributes, properties, properties, attributes, components, etc. disclosed herein with respect to various embodiments can be used with all other embodiments presented herein. Furthermore, it is recognized that any method described herein can be performed using any device suitable for performing the described steps.
[0119] While a number of embodiments and variations thereof have been described in detail, other modifications and methods of using them will become apparent to those skilled in the art. It should therefore be understood that various applications, modifications, materials, and substitutions can be made from the specific inventive disclosure herein, or equivalents, without departing from the scope of the claims.
Claims
1. 0.8% to 1.6% by weight of C; 14% to 26% by weight of Cr; 8% to 16% by weight of Mo; 2.38% by weight to 10% by weight of Nb+Ti; 2% by weight or less of impurities other than the above components; The balance consists of Ni and unavoidable impurities, At 1500K, A feedstock material configured to form a microstructure characterized by having at least 5 mole percent in total of hard phases having a Vickers hardness of at least 1,000, and the balance being a corrosion resistant matrix.
2. 0.84 wt.% to 1.56 wt.% C; 14% to 26% by weight of Cr; 8.4 wt% to 15.6 wt% Mo; 4.2% to 8.5% by weight of Nb+Ti.
3. 0.84 wt.% to 1.56 wt.% C; 14% to 26% by weight of Cr; 8.4 wt% to 15.6 wt% Mo; 4.2 wt.% to 7.8 wt.% Nb; 2. The feedstock of claim 1, comprising 0.35 wt.% to 0.65 wt.% Ti.
4. 1.08 wt.% to 1.32 wt.% C; 13% to 22% by weight of Cr; 10.8 wt% to 13.2 wt% Mo; 5.4 wt.% to 6.6 wt.% Nb.
5. The raw material according to any one of claims 1 to 4, wherein the raw material is a powder.
6. A hardfacing layer formed from the raw material according to any one of claims 1 to 4.
7. 7. The hardfacing layer of claim 6, wherein the hardfacing layer has a corrosion rate of less than 0.00254 mm / year in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61.
8. 8. The hardfacing layer of claim 7, wherein the hardfacing layer has a corrosion rate of less than 0.0020 mm / year in a 3.5% sodium chloride solution for 16 hours according to G-59 / G-61.
9. 7. The hardfacing layer of claim 6, wherein the hardfacing layer is applied in a hydraulic cylinder, a tension riser, a mud motor rotor, or an oil field component application.
Citation Information
Patent Citations
Nickel base alloy and stainless steel valve with nickel base alloy layer sealing surface, and production method thereof
CN101368239A
High temperature alloy
EP0057242A1
Tainetsutaimamochuzogokin
JP1976061424A
Abrasion resistant * corrosion resistant nickel base hard alloy
JP1980122848A
Ni-based alloy having excellent corrosion resistance and wear resistance
JP1989177330A